2015
DOI: 10.1177/1941406415602528
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding Attachment and Positioning Technique, Practices, and Knowledge of Related Issues Among Mothers in a Resettlement Colony of Delhi

Abstract: Breastfeeding is a crucial and unrivalled way of providing ideal food for the healthy growth and development of infants."

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
36
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(50 citation statements)
references
References 12 publications
6
36
1
1
Order By: Relevance
“…21 Mamta Parashar et al found correct attachment and positioning was in 7.5% of the mothers in an urban resettlement colony located in East Delhi. 22 Other comparable study by Coca et al (Sao Paulo, Brazil) and Kronborg et al also reported that parity was significantly associated with position and attachment. 14 However, Gupta et al from North India did not find any statistically significant association between parity, age of baby, literacy of mothers and effective breastfeeding.…”
Section: Discussionmentioning
confidence: 75%
“…21 Mamta Parashar et al found correct attachment and positioning was in 7.5% of the mothers in an urban resettlement colony located in East Delhi. 22 Other comparable study by Coca et al (Sao Paulo, Brazil) and Kronborg et al also reported that parity was significantly associated with position and attachment. 14 However, Gupta et al from North India did not find any statistically significant association between parity, age of baby, literacy of mothers and effective breastfeeding.…”
Section: Discussionmentioning
confidence: 75%
“…Ensuring universal breastfeeding can avert 823,000 under-five children deaths and 20,000 breast cancer deaths every year [9]. However, most mothers do not realize breastfeeding technique as a learned skill that needs practice and patience [10].…”
Section: Introductionmentioning
confidence: 99%
“…Attachment indicates whether the infant has enough areola and breast tissue in the mouth, and suckling denotes to the drawing of milk into the mouth from the nipple [11]. Improper positioning, attachment, and suckling are constructs for ineffective breastfeeding technique (IBT), which results in inadequate intake of breast milk that leads to poor weight gain, stunting, and declines immunity [10,12]. The 2019 mini-Ethiopian demographic health survey (MEDHS) reported that 37%, 21% and 7% of under-five children are stunted, underweight and wasted respectively [13].…”
Section: Introductionmentioning
confidence: 99%
“…Parashar M et al study showed that only 7.5% of the mothers were practicing correct breastfeeding attachment and positioning technique. 23 In our study, we found that 55.98% Primiparus knew about the advantage of early and exclusive breast feeding. 80.86% women had received antenatal counselling on breastfeeding and only 58.85% knew that exclusive breastfeeding should be continued for 6 months.…”
Section: Discussionmentioning
confidence: 70%
“…It was found that initiation was delayed because of the presence of some beliefs and practices enforced by elder persons, such as mother-inlaw. 23 In our study, 82.77% mothers preferred the side lying position compared to 17.23% who practiced breast feeding in standard cradle hold position. Similar findings were observed in Dasgupta et al where 74% mothers were practicing correct technique.…”
Section: Discussionmentioning
confidence: 80%